2008
DOI: 10.1038/onc.2008.204
|View full text |Cite
|
Sign up to set email alerts
|

Mutated in colorectal cancer, a putative tumor suppressor for serrated colorectal cancer, selectively represses β-catenin-dependent transcription

Abstract: Mutated in colorectal cancer (MCC ) was originally identified as a candidate gene for familial adenomatous polyposis (FAP) but further study identified adenomatous polyposis coli (APC) as responsible for FAP and the physiologic/pathologic roles of MCC remained poorly understood. Recently, MCC promoter methylation was discovered as a frequent early event in a distinct subset of precursor lesions and colorectal cancer (CRC) associated with the serrated CRC pathway. Here we provide the first evidence of the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(136 citation statements)
references
References 36 publications
5
127
2
2
Order By: Relevance
“…In immunohistochemical studies, strong APC expression was observed in most SSA/Ps, whereas MCC expression was reported to be frequently lost. 21,22 MCC methylation is more common in SSA/Ps (89%) than in adenomas (35%). 20 Our study showed that MCC was methylated in 15% of SSA/Ps, and in all of SSA/Ps with high-grade dysplasia and those with submucosal carcinoma, but only 11-16% of the adenoma series.…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
See 1 more Smart Citation
“…In immunohistochemical studies, strong APC expression was observed in most SSA/Ps, whereas MCC expression was reported to be frequently lost. 21,22 MCC methylation is more common in SSA/Ps (89%) than in adenomas (35%). 20 Our study showed that MCC was methylated in 15% of SSA/Ps, and in all of SSA/Ps with high-grade dysplasia and those with submucosal carcinoma, but only 11-16% of the adenoma series.…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
“…As a result, free b-catenin accumulates and translocates into the nucleus and subsequently binds to the T-cell factor/ lymphoid enhancer factor initiating transcription of target genes such as c-myc. 17 b-Catenin is also regulated by various other components such as mutated in colorectal cancer (MCC) and secreted frizzled-related proteins (SFRPs); 17 the functions of MCC or SFRPs as negative regulators of WNT/b-catenin signaling may have important implications in genesis of colorectal carcinomas [19][20][21] as well as SSA/P. 22 AXIN2 has been found to be silenced, apparently as a result of methylation of its promoter region, specifically in colorectal carcinomas with high levels of microsatellite instability.…”
mentioning
confidence: 99%
“…In overexpression studies, MCC was shown to physically associate with β-catenin in the nucleus to negatively regulate canonical TCF/ LEF-dependent Wnt signaling and to inhibit cell proliferation (Fukuyama et al, 2008;Matsumine et al, 1996). More recently, MCC was observed to be mainly localized in the cytoplasm of colon cancer cell lines but translocated to the nucleus in response to DNA damage to induce cell cycle arrest (Pangon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MCC has previously been reported to antagonize canonical Wnt signaling in CRC cell lines (Fukuyama et al, 2008). We evaluated whether Mcc can inhibit β-catenin-dependent activation of the −0.8 kb Xenopus Siamois luciferase reporter, and found that Mcc overexpression has no effect on reporter activation -neither synergy nor inhibition -upon co-injection of mRNA encoding either the canonical Wnt8 ligand, which normally suppresses dorsal organizer genes and patterns ventrolateral mesoderm, or its effector β-catenin (Baker et al, 2010) (supplementary material Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation